Toxic Leadership in Education: A Systematic Review - Birol Başkan (International Journal of Educational Administration, Management, and Leadership, 2020)
There has been sparse research explicitly looking at toxic leadership, a more complex and comprehensive destructive leadership style in higher education settings, despite the breadth of literature on destructive leadership styles and their impact on organizational culture, mission, and individuals. With the introduction of the term “toxic leadership” in 1996, the corporate world and military agencies began to examine whether leadership could lead to a toxic culture. As of 2007, studies have been unable to connect the concept of learning in higher education systems to the phenomenon of "social learning." To better understand how studies have changed since they were conducted in the 2000s, the authors use their analysis of the literature on toxic leadership in higher ed from three different perspectives: 1) Understanding how toxic leadership affects organizational culture and employee morale. 2) Summarizing the role of toxic leadership in shaping the environment in which employees operate. 3) Speculating on what can be done to manage the risk of building and sustaining such environments.